Program Spectra Analysis with Theory of Evidence. (15th February 2012) - Hewett Hewett, Rattikorn Rattikorn
Abstract : This paper presents an approach to automatically analyzing program spectra, an execution profile of program testing results for fault localization. Using a mathematical theory of evidence for uncertainty reasoning, the proposed approach estimates the likelihood of faulty locations based on evidence from program spectra. Our approach is theoretically grounded and can be computed online. Therefore, we can predict fault locations immediately after each test execution is completed. We evaluate the approach by comparing its performance with the top three performing fault localizers using a benchmark set of real-world programs. The results show that our approach is at least as effective as others with an average effectiveness (the reduction of the amount of code examined to locate a fault) of 85.6% over 119 versions of the programs. We also study the quantity and quality impacts of program spectra on our approach where the quality refers to the spectra support in identifying that a certain unit is faulty. The results show that the effectiveness of our approach slightly improves with a larger number of failed runs but not with a larger number of passed runs. Program spectra with support quality increases from 1% to 100% improves the approach's effectiveness by 3.29%.